2008
DOI: 10.1007/s10439-008-9600-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Experiment of Transient and Steady Characteristics of Ultrasonic-Measurement-Integrated Simulation in Three-Dimensional Blood Flow Analysis

Abstract: In ultrasonic-measurement-integrated (UMI) simulation of blood flows, feedback signals proportional to the difference of velocity vector optimally estimated from Doppler velocities are applied in the feedback domain to reproduce the flow field. In this paper, we investigated the transient and steady characteristics of UMI simulation by numerical experiment. A steady standard numerical solution of a three-dimensional blood flow in an aneurysmal aorta was first defined with realistic boundary conditions. The UMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…This relation agrees with the empirical relation obtained in a former study [25]. In summary, the destabilization phenomenon of existing MI simulation is ascribed to the fact that a large feedback signal in the source term determines the leading term of the numerator of the coefficient for the successive change in the iterative calculation, and, therefore, divergence occurs with a coefficient larger than 1 or with a feedback gain larger than the critical value.…”
Section: Stabilizationsupporting
confidence: 80%
See 3 more Smart Citations
“…This relation agrees with the empirical relation obtained in a former study [25]. In summary, the destabilization phenomenon of existing MI simulation is ascribed to the fact that a large feedback signal in the source term determines the leading term of the numerator of the coefficient for the successive change in the iterative calculation, and, therefore, divergence occurs with a coefficient larger than 1 or with a feedback gain larger than the critical value.…”
Section: Stabilizationsupporting
confidence: 80%
“…The transient characteristics of the UMI simulation were evaluated by the time constant or equivalently by the frequency response to the oscillating flow, and the steady characteristics were evaluated by the steady state error of the velocity vectors in an aneurysm. Velocity error vectors against the standard solution are shown in Figure 17 [25]. In the initial state, the result is the same as that of the ordinary simulation with large error vectors.…”
Section: Blood Flowssupporting
confidence: 63%
See 2 more Smart Citations
“…In our previous studies, a two-dimensional UMI simulation using real ultrasound color Doppler images was conducted [19]. The transient and steady characteristics of UMI simulation and the efficiency of feedback to reproduce unsteady threedimensional hemodynamics were investigated by numerical experiments [21][22][23]. Those studies revealed that the UMI simulation improved computational accuracy in comparison with the ordinary simulation, making the computational velocity vector field approach that of a model solution of real blood flow.…”
Section: Introductionmentioning
confidence: 95%